Reshoring: Myth or Reality? - De Backer, Koen (OECD Science, Technology and Industry Policy Papers, 2016)
The news that companies in OECD economies are increasingly bringing manufacturing activities back home has attracted a lot of attention in recent years. Headline cases of a number of large multinational companies have given increased visibility to the phenomenon of reshoring in the economic press, academic research and policy discussions.. The debate on re-shoring (often also called "backshoring", "nearshoring", "onshoring") is very lively with some even arguing that the time of offshoring has come to an end. But considerable disagreement exists about how important this trend actually is for economies in particular the number of jobs that reshoring is supposed to bring back. While policy makers in OECD economies hope that reshoring might help to revitalise their slumping manufacturing industries, the rationale for policy measures around reshoring is not clear-cut